Predictors of behavioral cancer risk factors and preventive behaviors among Nebraskans. (December 2022) - Ratnapradipa, Kendra; Watanabe-Galloway, Shinobu; Hymel, Emma; High, Robin; Farazi, Paraskevi A.
Abstract: Background: The overall incidence rate of cancer in Nebraska is higher than the national average with cancer being the second leading cause of death in the state. Interventions are required to reduce the cancer burden; however, further research is first needed to identify behavioral cancer risk factors and preventive behaviors among Nebraskans that can be targeted. Methods: A statewide cross-sectional survey of Nebraskans aged 19 and older was conducted in 2019 using an address-based sampling method (n = 1640). Multivariable logistic regression was used to examine factors associated with being up-to-date on cancer screening and with behavioral cancer risk factors and preventive behaviors. Results: 93.42% of Nebraskans did not meet the daily recommended consumption of fruits and vegetables, and 71.51% did not meet weekly physical activity guidelines. The proportion of adults up to date on cancer screening was 64.57% for breast, 68.83% for cervical, 69.01% for colorectal, and 24.07% for skin cancers. Individuals 65–74 (OR: 3.40, 95% CI: 1.52–7.62) and 75 or older (OR: 3.30, 95% CI: 1.35–8.07) were more likely to be current with their colorectal cancer screening compared to ages 50–64. Hispanics were less likely to be current with mammograms (OR: 0.06, 95% CI: 0.01–0.71) and ever screened for cervical cancer (OR:0.13, 95% CI: 0.02–0.94) compared to Non-Hispanic Whites. Conclusions: Disparities in cancer screening and risk and preventive behaviors exist in Nebraska. Impact: The study highlights a need for continuing efforts to improve preventive cancer behaviors for the entire population as well as some high-risk populations in Nebraska. Highlights: Disparities in cancer screening and risk and preventive behaviors exist in Nebraska. There is a need for continuing efforts to improve preventive cancer behaviors for the entire population as well as some high-risk populations in Nebraska.